2004
DOI: 10.1897/03-110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sediment on the fate of metolachlor and atrazine in surface water

Abstract: In aquatic environments, pesticides can partition between the dissolved phase and particulate phase depending on the type of suspended sediment present and the physical and chemical properties of the pesticides and water. Particulate matter and sediment can alter the bioavailability of contaminants to organisms and therefore influence their toxicity and availability for microbial degradation. Experiments were conducted to determine the degradation of atrazine (6-chloro-N-ethyl-N′-(1-methylethyl)-1,3,5-triazine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…44) Triazine herbicides were mostly resistant to biodegradation in river waters, 49,90,113,118) but some of them were degraded at moderate rates after a long lag period. 119) By using 14 C-labeled atrazine (52), Rice et al 120) have reported about 10% contribution of biotic processes in its degradation via N-dealkylation and hydrolytic dechlorination.…”
Section: Organophosphorus Pesticides (Ops)mentioning
confidence: 99%
See 1 more Smart Citation
“…44) Triazine herbicides were mostly resistant to biodegradation in river waters, 49,90,113,118) but some of them were degraded at moderate rates after a long lag period. 119) By using 14 C-labeled atrazine (52), Rice et al 120) have reported about 10% contribution of biotic processes in its degradation via N-dealkylation and hydrolytic dechlorination.…”
Section: Organophosphorus Pesticides (Ops)mentioning
confidence: 99%
“…46,107,120,145,156) The catalytic hydrolysis by clay minerals and metal cations from sediments is assumed, but it is considered limited to some types of pesticides. 17) An insignificant sediment effect for an ionic pesticide that is slowly biodegraded was also observed.…”
Section: Sedimentmentioning
confidence: 99%
“…loss of atrazine and metolachlor in the presence of natural sediments, attributing this to more rapid biodegradation as well as sequestration by the sediments (Rice et al, 2004). Up to 10% of the herbicides were physically associated with sediments in that study, highlighting differences in the potential of sediments (affected by type) on removal of herbicides from the water column and their potential bioavailability.…”
Section: Discussionmentioning
confidence: 75%
“…Up to 10% of the herbicides were physically associated with sediments in that study, highlighting differences in the potential of sediments (affected by type) on removal of herbicides from the water column and their potential bioavailability. The inclusion of sterile sediment treatments allowed Rice et al, (Rice et al, 2004) to postulate that the presence of sediments may also influence non-biotic degradation rates. For example, humic acids often associated with sediments have been shown to increase photodegradation and hydrolysis of a range of contaminants (Cessna, 2008;Lin et al, 2008;Steen et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation